Efficacy of an advanced hybrid closed-loop system in a patient with type 1 diabetes and intellectual disability: a case report - Taka, Hidetsugu; Sugai, Keiji; Shikuma, Jumpei; Suzuki, Ryo (Frontiers in Endocrinology, 2025)
Recent advances in automated insulin delivery (AID) system have been remarkable. The advanced hybrid closed-loop (AHCL) system made it easier to achieve optimal glycemic targets. According to previous studies, the AHCL system achieves relatively good glycemic control without strict carbohydrate input. These studies suggested that AID systems potentially improve glycemic control among patients with difficulty with self-management. However, few studies have focused on the efficacy of the systems among these patients. We present a case of a 30-year-old woman with type 1 diabetes and intellectual disabilities (full-scale intelligence quotient = 67) due to Shwachman-Diamond syndrome. While using a sensor-augmented pump with the predictive low glucose suspend system, her glycated hemoglobin levels consistently ranged from 9.0% to 10.0%, and she experienced frequent hospitalizations due to diabetic ketoacidosis. Stepping up to a hybrid closed-loop system achieved better glycemic control and prevented hospitalizations due to diabetic ketoacidosis. Finally, the patient achieved optimal glycemic control through the use of the AHCL system. Our case highlights the potential of AID systems in patients with type 1 diabetes and self-management difficulties, including those with intellectual disabilities.